Methods used by small-scale mangrove crab (Scylla spp.) producers to maintain production during the southwest monsoon season in the Philippines - Bolaños, Jannella L. (Animo Repository, 2023)
The southwest monsoon season coincides with the landfall of tropical cyclones in the Philippines. This increases the frequency of extreme weather events like heavy rainfall and storm surges. While it is expected for the production of mangrove crabs to decline during unfavorable weather conditions, annual production data shows otherwise. This implies that the traditional ecological knowledge and strategies used by local crab growers ensure that their harvest is sustained. To consolidate these measures, 25 pen and pond operators from ten regions in the country were interviewed. Performing emergency harvests, planning the timeline for the harvest and dropping of seedstock, reinforcing dikes, investing in culture equipment, decreasing seedstock input, monitoring pond perimeter, and using a net enclosure were the common measures practiced by the participants to prepare for the onset southwest monsoon. Methods unique to regions that maintained their harvest yield during this monsoon period include increasing the depth of their pond, blocking off all tunnels and drainage in the pond, investing in commercial feeds and fertilizers, planting mangroves, draining the pond for emergency harvests, and utilizing crab cages. Five field experts were interviewed to supplement the insights of the crab growers and to understand the current trajectory of the mangrove crab industry. Data from this study can be used by local government units to develop appropriate assistance schemes for resident aquaculture producers and coastal communities. Novice crab growers may adopt and reinvest in the consolidated measures to overcome seasonal fluctuations.